Luka kompetencyjna mistrzów w rzemiosłach budowlanych w świetle wyników projektu „ENCORE - Stępnikowski, Andrzej Wojciech; Ślusarczyk, Michał (Edukacja ustawiczna dorosłych : kwartalnik naukowo-metodyczny, 2022)
This article summarises the results of the ENCORE project ‚ Environmental education model for masters and stakeholders involved in construction and renovation’. The project aimsto lay the foundation for standards of the changes in examination requirments standards bydemonstrating the existence of a competence gap among craftsmen. This gap is related to theirawareness of the new challenges posed to them by the Renovation Wave. In this article, basedon the conclusions drawn from our own research, we present a initial proposal for changing theexaminational requriments in building crafts.